2012
DOI: 10.3109/13697137.2012.682746
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function, mood and menopause symptoms in Lithuanian postmenopausal women

Abstract: HT increased chances for better sexual desire, lubrication, satisfaction, less pain and lower depression symptoms in postmenopausal women, even when the results were adjusted by age. HT did not improve sexual arousal, orgasm, menopausal and anxiety symptoms. Depression, anxiety, menopausal symptoms and age were the main risk factors for the possible development of sexual dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
2
23
1
2
Order By: Relevance
“…The negative effect of depression on sexual activity or satisfaction confirms findings in other studies for women in both early and late postmenopause [7,21,24,25].…”
Section: Discussionsupporting
confidence: 89%
“…The negative effect of depression on sexual activity or satisfaction confirms findings in other studies for women in both early and late postmenopause [7,21,24,25].…”
Section: Discussionsupporting
confidence: 89%
“…Reduction in sexual pleasure or decreased libido, as one of its first symptoms, had a high prevalence in the general population of women (32). In the study by Jonusiene et al (33), the main risk factors for the onset of sexual dysfunction were reported to be depression, anxiety, menopausal symptoms, and age. Avellanet et al (32) also showed that depression symptoms and signs were significantly associated with decreased sexual pleasure.…”
Section: Discussionmentioning
confidence: 98%
“…O uso de terapia de reposição hormonal por seis meses ou mais não se associou à disfunção sexual na atual pesquisa. Apesar de vários estudos mostrarem melhora da função sexual com o uso da terapia de reposição hormonal [30][31][32][33] , uma recente revisão sistemática da Biblioteca Cochrane 34 , envolvendo 27 estudos com 16.393 mulheres, não apontou melhora da função sexual no subgrupo de mulheres com mais de 5 anos de finalização da menstruação, independente dos sintomas da menopausa. A revisão apresenta uma melhora de magnitude pequena ou moderada, apenas quando a terapia de reposição hormonal é utilizada em mulheres com sintomas de menopausa ou pós-menopausa nos cinco primeiros anos de amenorreia 34 .…”
Section: Discussionunclassified